2021
DOI: 10.1021/acsnano.0c10141
|View full text |Cite
|
Sign up to set email alerts
|

Restoring Tactile Sensation Using a Triboelectric Nanogenerator

Abstract: Loss of tactile sensation is a common occurrence in patients with traumatic peripheral nerve injury or soft tissue loss, but as yet, solutions for restoring such sensation are limited. Implanted neuro-prosthetics are a promising direction for tactile sensory restoration, but available technologies have substantial shortcomings, including complexity of use and of production and the need for an external power supply. In this work, we propose, fabricate, and demonstrate the use of a triboelectric nanogenerator (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 51 publications
(95 reference statements)
0
26
0
Order By: Relevance
“…However, for future clinical trials, we need to admit that, just as our experimental results showed, the current the TENG-based self-powered neuroprosthetics still have a long way to replace the current electrical stimulation paradigm. Other research teams also demonstrated the TENGbased self-powered neuroprosthetics methods, [38,40] but we need to face the fact that most neural modulation applications such as epidural electrical stimulation, deep brain stimulation, vagus nerve stimulation. All these functional stimulations recommended pulse frequencies are higher than the current pulse frequency generated by the TENG devices.…”
Section: Discussionmentioning
confidence: 99%
“…However, for future clinical trials, we need to admit that, just as our experimental results showed, the current the TENG-based self-powered neuroprosthetics still have a long way to replace the current electrical stimulation paradigm. Other research teams also demonstrated the TENGbased self-powered neuroprosthetics methods, [38,40] but we need to face the fact that most neural modulation applications such as epidural electrical stimulation, deep brain stimulation, vagus nerve stimulation. All these functional stimulations recommended pulse frequencies are higher than the current pulse frequency generated by the TENG devices.…”
Section: Discussionmentioning
confidence: 99%
“…Shlomy et al developed an integrated tactile TENG that was implanted under the skin. 238 The electrical potential was delivered to healthy sensory nerves to mimic the tactile sensation by activating them. The current solutions developed for the purpose of in and on body electrical stimulation (ES) lack autonomous qualities necessary for comfortable, practical, and self-dependent use.…”
Section: Energy and Environmental Science Reviewmentioning
confidence: 99%
“…Implantable nerve prostheses represent a promising direction, but these still possess some disadvantages, including the complexity of their use scenarios and the requirement of bloated external power supplies. Therefore, to solve this problem, Shlomy et al proposed triboelectric nanogenerators (TENG-IT) with simple structures that were self-powered, biocompatible, and highly customizable for tactile restoration [ 70 ]. PDMS, nylon (Ny), and cellulose acetate butyrate (CAB), which has the advantages of flexibility and biocompatibility, were selected as friction layers in this device, with PDMS being a negative layer, and Ny and CAB being positive layers.…”
Section: Long-term Self-treatment Equipmentmentioning
confidence: 99%
“…TENG-IT is implanted under the skin (desensitized fingers). Reprinted with permission from [ 70 ]. 2021, ACS.…”
Section: Figurementioning
confidence: 99%